A structural analysis of foreign exchange markets in sub-Saharan Africa - Annina Kaltenbrunner; Daniel Perez Ruiz; Anjelo Okot (European Investment Bank (EIB), 2022)
This paper presents detailed insights into the microstructural characteristics of several African Lower and Lower-Middle Income Countries (LLMICs) foreign exchange markets and the implications of these characteristics for macroeconomic management. It draws on 13 semi-structured interviews with 17 foreign exchange experts in central banks, banks, non-bank financial institutions, and research institutions in selected case studies (Ghana, Kenya, Malawi, Sierra Leone, Uganda, and Zambia) and the City of London. The results show that whilst most case study countries have functioning foreign exchange interbank markets, these markets are oftentimes characterised by low, volatile and "lumpy" liquidity. These liquidity dynamics and uncertainty about future foreign exchange flows can lead to FX hoarding among foreign exchange market participants, further depriving the official foreign exchange market of liquidity. Moreover, they provide those with access to FX liquidity with significant market power and the potential to affect price dynamics. These microstructural characteristics, in turn have meant that central banks in African LLMICs remain key agents in foreign exchange markets to manage scarce and volatile liquidity patterns. At the same time though, these microstructural weaknesses complicate central banks' ability to deal with volatile foreign exchange availability and structural depreciation pressures. Whereas hoarding behaviour reduces the central bank's access to foreign exchange, low trust in domestic currencies puts serious limits on the extent of nominal depreciations central banks will be able and willing to tolerate. Overall, the results show the difficulties of moving towards floating exchange rates in the context of African LLMICs, characterised by concentrated export structures, low trust in their currencies, and shallow domestic financial markets.
Keywords: 330